THE PLACE OF ACCOUNTING THEORY AND ACCOUNTING PRACTICE IN THE MANAGEMENT SYSTEM OF BUSINESS ENTITIES IN UKRAINE - HEVLYCH, Larysa (Herald of Khmelnytskyi National University. Economic sciences, 2024)
The paper hypothesizes that understanding the essence, common features and differences of accounting theory and accounting practice can improve information support for management decisions and optimize educational programs for training specialists in the specialty “Accounting and taxation” for the domestic economy. The purpose of the work is to study the relationship between the theoretical essence and the practical implementation of accounting from the point of view of the impact on the decision-making process of domestic economic entities. The work provides a comparative description of the essence, purpose, functions, features, methods, needs in the regulation of accounting theory and accounting practice, based on which their common features and differences are highlighted. In particular, the coincidence of the purpose and needs of the regulation and the wider coverage of the accounting practice of functions, subjects and methods were ascertained. According to the results of the study, it is proven that the identification of the essence of accounting practice helps to formalize the process of making managerial decisions at the micro level by increasing the awareness of managers and other users of accounting data. This contributes to the effective management of the business entity and the validity of decisions made regarding it by external users. It was established that understanding the essence of the professional activity of a graduate of specialty 071 “Accounting and taxation” of the bachelor’s degree allows to optimize educational programs due to consideration of the peculiarities of accounting practice. It was established that the requirements of the labor market, which currently expects mathematical and digital competences from economists in the field of accounting and taxation, have a significant impact on the content of accounting practice. The work examines the educational components of the “Digital Accounting and Taxation” educational program of the bachelor’s degree of Vasyl’ Stus Donetsk National University. Conclusions are drawn, directions for further research are outlined.
Keywords: accounting theory; accounting practice; management; business entity